Two new species of the genus Seracamaurops Winkler (Coleoptera: Staphylinidae: Pselaphinae: Amauropini) from Montenegro - Lohaj, Roman; Pavićević, Dragan; Lakota, Ján (Biologia Serbica, 2023)
Nearly two hundred years of continuous and systematic research in the Dinaric karst subterranean habitats has resulted in the recognition of more than 400 narrowly distributed and specialized subterranean beetles. The majority of these belong to the families Leiodidae (tribe Leptodirini) and Carabidae (tribe Trechini). Although Staphylinidae is one of the most wide-spread and species rich families of Coleoptera in the world, only a small portion of these species have successfully adapted to subterranean habitats. In this contribution, we present a description of two new species of subterranean Pselaphinae, Amauropini from Montenegro; Seracamaurops subgenus Seracamaurops s. str.: S. (S.) delici sp. nov. from Kučke planine Mts. and S. (S.) rumijaensis sp. nov. from Rumija Mt. Both species are described, illustrated and compared with related species. They are clearly distinguished from all known Seracamaurops species by several taxonomic characters, i.e. shape of the aedeagus, the female pygidium and fissures of the last tergite in both sexes. An annotated catalogue of the genus Seracamaurops is also presented.